Preemption and re-routing control strategy for resource provisioning and path selection in connection oriented networks - Lau, Chun Hau (2008)
This thesis focuses on the preemption issues in connection-oriented networks, e.g. MPLS and ATM. Preemption mechanism primarily resides in the network management realm, where it functions by tearing down existing lower priority connections in order to provide resources for the higher priority connections. Generally, it is activated when the network experiences high congestion due to competitions between different connections and network resources must be provided to satisfy the new mission critical connections. However, by giving these limited resources to the critical connections through preemption, the duration spent and work done for the preempted connections are wasted. This could lead to lower network throughput as well as higher service interruption. Our objective is to minimize this service disruption and loss of throughput. The general strategy is to provide re-routing capability to the existing connections, such that, these connections are re-routed before being torn down. By re-routing the connections as far as possible, the author shows that the network throughput loss is minimized while the service disruption is reduced significantly. Subsequently, this strategy is extended by using the preemption mechanism as an active entity for network path selection.